The Last Years of Robert E. Lee : From Gettysburg to Lexington. - Savage, Douglas (Taylor Trade Publishing, 2016)
This book details Lee's life from Gettysburg to his death just five years after the South's surrender at Appomattox. After the war, Lee sought to heal the nation, even meeting with his rival, Ulysses S. Grant, while he occupied the White House. Leaving his military life behind, Lee went on to become president of Washington College.